Genome sequencing enhances the diagnostic yield and expands the genetic landscape of male breast cancer - Wen Wen; Sen Zhao; Yiwen Jiang; Chengzhu Ou; Changyuan Guo; Ziqi Jia; Jiayi Li; Yansong Huang; Hengyi Xu; Pengming Pu; Tongxuan Shang; Lin Cong; et al. (Genetics in Medicine Open)
Purpose: To understand the broader genetic landscape of male breast cancer (MBC), focusing on the utility of genome sequencing (GS) beyond BRCA1/2 (HGNC: 1100, 1101) variants. Methods: Twenty-four patients with MBC underwent a multistep genetic analysis. Initial screening targeted BRCA1/2 variants followed by GS to identify pathogenic/likely pathogenic germline variants through a 3-tiered classification. Polygenic risk score analysis was further incorporated using a model for female breast cancer with 2666 noncancer controls. Exome sequencing was used to transition from germline to somatic investigations, assessing second-hit variant and mutational signatures. Results: The GS analysis unveiled previously unrecognized pathogenic/likely pathogenic germline variants in BARD1, ATR, BRIP1, and CHEK2 (HGNC: 952, 882, 20473, 16627) among 21 BRCA1/2-negative patients with MBC, elevating the diagnostic yield from 12.5% to 33.0% in all MBC. Elevated average polygenic risk score was noted compared with controls, with a significant correlation to early-onset MBC when combined with high-penetrance germline pathogenic variants (P = 1.10 × 10−4). Exome sequencing analysis further identified significant somatic oncogenic drivers and revealed a dominant mutational signature SBS3 across BRCA1/2-negative samples, reinforcing the contribution of omologous recombination deficiency underlying the MBC development. Conclusion: Our findings extended the MBC genetic spectrum beyond BRCA1/2 and highlighted the intricate interplay of monogenic and polygenic predispositions, presenting a comprehensive MBC genomic profile.